Hustle culture and stress levels among start-up employees in the industry 4.0 era - An Nissa Aulia Rahmi; Jojor Putrini Sinaga; Ita Armyanti (Malahayati International Journal of Nursing and Health Science, 2026)
Background: The emergence of industry 4.0 in Indonesia has transformed various aspects of life, including employment systems and workplace dynamics. This industrial revolution integrates humans, machines, and internet-based technologies into production processes through innovative methods. Along with the rapid growth of start-up companies, new work patterns have emerged, including a culture of excessive productivity known as hustle culture, which may affect workers’ mental health. Purpose: To analyze the relationship between hustle culture and stress levels among start-up employees in the industry 4.0 era. Method: A literature review approach was employed analyzing 7 scientific journals on hustle culture, occupational stress, and employment transformation in the industry 4.0 era. Relevant articles were selected and reviewed to identify the impact of hustle culture on workers’ stress levels and mental well-being. Results: The hustle culture was associated with increased stress levels among workers. High job demands, pressure for extreme productivity, and imbalance between work and personal life were identified as major contributing factors to work-related stress, burnout, depression, and reduced psychological well-being. Conclusion: Hustle culture has a significant impact on workers’ stress levels in the industry 4.0 era. Organizations should implement effective work stress management and create a supportive work environment that promotes work–life balance and mental well-being. These efforts may reduce the negative effects of occupational stress while improving productivity, job satisfaction, and employee retention.